PENGGUNAAN MEDIA PEMBELAJARAN POP UP BOOK UNTUK MENINGKATKAN PEMAHAMAN BELAJAR SISWA MI DALAM MENGELOMPOKKAN JENIS TUMBUHAN - Muhammad Kholil; NurFadilatun Nisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low concentration and interest in learning of students causes the results of student learning achievement to be less than optimal. This happens because of the lack of learning media used by teachers in delivering the material so that learning is less effective. In this case, the researcher wants to implement and test the Pop up book learning media to improve students' learning understanding so that students can understand the material easily, especially in the material